2021
DOI: 10.1111/jace.17988
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties and phase transition of doped single crystals and polycrystals of Bi2Te3

Abstract: The temperature dependences of the electrical conductivity (T), Seebeck coefficient (T), and heat capacity C p (T) of polycrystalline samples of Bi 2 Te 3 , Bi 2 Te 3 +1%CuI, and Bi 2 Te 3 +1%(CuI+1/2Pb) are investigated in the temperature range below room temperature. Based on the temperature dependences of all investigated physical properties, it is discovered that phase transition occurs at 120-200 K. Investigation of single crystals shows that anomalies in the electrical resistivity ( (T) = 1∕ (T)) occur o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…According to experimental data and preliminary theoretical calculations [4,[28][29][30][31][32][33][34][35][36][37][38] layered transition metal dichalcogenides are the excellent candidates for efficient thermoelectric energy converters. Our investigations of layered chalcogenides have demonstrated that effective ways to improve thermoelectric properties are substitutions in sublattices and, as a result, the changes in the morphology of crystallites in bulk sample [3,29,[32][33][34]39].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…According to experimental data and preliminary theoretical calculations [4,[28][29][30][31][32][33][34][35][36][37][38] layered transition metal dichalcogenides are the excellent candidates for efficient thermoelectric energy converters. Our investigations of layered chalcogenides have demonstrated that effective ways to improve thermoelectric properties are substitutions in sublattices and, as a result, the changes in the morphology of crystallites in bulk sample [3,29,[32][33][34]39].…”
Section: Introductionmentioning
confidence: 96%
“…Single crystals in comparison with polycrystals have better thermoelectric properties [1][2][3][4][5][6][7]. But high cost and technological difficulties limit their use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization of one parameter of thermal conductivity or electrical conductivity usually causes the reduction of the other parameter. In recent years, compared with intermetallic thermoelectric compounds, such as Bi 2 Te 3 , [3] PbTe, [4] etc., thermoelectric oxide material Ca 3 Co 4 O 9 (abbreviated as CCO) has attracted extensive attention because of its good stability, convenient preparation, green environmental protection and low cost. [5] At present, the ZT value of polycrystalline Ca 3 Co 4 O 9 still cannot meet the requirements of practical application, which limits its commercial applica-tion.…”
Section: Introductionmentioning
confidence: 99%
“…3 Co 4 O 9 and can be regarded as spherical particles. The effect of carbon nanotube addition on the effective thermal conductivity of Ca 3 Co 4 O 9 material can be discussed by using the model of formula(2).…”
mentioning
confidence: 99%